An Examination of the Dental Utilization Practices of Adult Survivors of Childhood Cancer: a Report from the Childhood Cancer Survivor Study - Mark W. Yeazel, MD, MPH; James G. Gurney, PhD; Kevin C. Oeffinger, MD; Pauline A. Mitby, MPH, Ann C. (Blackwell Synergy, 2004)
This study characterized the self-reported dental utilization practice of long-term survivors of childhood cancer, a group at increased risk for treatment-induced dental abnormalities.